Development and characterization of a monoclonal antibody against the tube precipitin antigen of Coccidioides immitis. - Dolan, M J (1989)
Primary infection with Coccidioides immitis is commonly accompanied by the production of an immunoglobulin M precipitin antibody which is detected by the tube precipitin (TP) assay or by the immunodiffusion assay for TP antibody (IDTP assay). In the present investigation, spleen cells from spherulin-immunized BALB/c mice were fused with SP2/O Ag14 myeloma cells, and the resulting hybridomas were screened for antibody to the IDTP antigen by using an enzyme-linked immunosorbent assay. Positive hybridomas were cloned by limiting dilution and injected into pristane-primed mice for ascites production. Characterization of antibody reactivity was accomplished with the IDTP assay, two-dimensional immunoelectrophoresis, and immunoblotting. An immunoglobulin G1 monoclonal antibody which reacts with the IDTP antigen of C. immitis is described. The epitope that is recognized by the monoclonal antibody is also present, but to a lesser extent, on a second coccidioidal antigen which has been designated antigen 2. The monoclonal antibody was not reactive in immunoblots of histoplasmin or blastomycin, indicating that the epitope recognized by this antibody may be specific for C. immitis.